Linking Past and Present: A Critical Analysis of the US-Libya Intervention in Relation to Proposed US Military Support for Nigeria - Chuks, Menyeneabasi Franklin; Joshua, Timothy Sunday (African Journal of Stability and Development (AJSD), 2025)
This study investigates how the legacy of the United States intervention in Libya continues to shape current debates about proposed US military support for Nigeria’s security problems. It looks at the political, security and regional consequences of the Libya crisis and shows how the collapse of state institutions in 2011, along with the spread of armed groups across the Sahel, reshaped West Africa’s security environment. The study uses a qualitative design that draws on policy documents, scholarly work and interviews with experts to trace how lessons from Libya influence the thinking of Nigerian policymakers, civil society actors and security analysts as they weigh the risks and possible gains of deeper US involvement. The analysis brings forward the concerns that often guide these discussions, including fears over sovereignty, long-term stability and the unintended effects that external military actions can trigger. At the same time, it considers the view that carefully structured US support could strengthen Nigeria’s counter-banditry and counter-terrorism efforts if managed within clear political and operational boundaries. By connecting a past intervention to a present policy dilemma, the study shows how historical experience shapes security choices in Nigeria today. The findings help clarify the conditions under which external assistance can support, or undermine, national security goals in fragile and conflict-prone settings.